Academic freedom as a university’s language of self-description - V. S. Nikolsky (Высшее образование в России)
The key theme of the article is a comprehension of the idea of academic freedom inconditions of socio-cultural context changing. The author adduces a number of arguments forsupporting the principle of academic freedom as a necessary condition for scientific search and finding scientific truth. The academic freedom is treated as a manifestation of academic activities, while the University is viewed as an institutialization of the principle of academic freedom.